Larger than life: Linguistic aspects as a strategy for provoking hedonism in car slogans - Aris Munandar; Emma Natasha Octoveria (Universitas Syiah Kuala, 2025)
Advertisements sell fantasy rather than just products, with their slogans creating lasting impressions of fantasy in the minds of target consumers. This research aims to explore how English slogans in Indonesian car advertisements provoke hedonism through specific syntactic forms and illocutionary forces. Through a qualitative analysis of syntactic and pragmatic aspects, the proportion of syntactic forms, illocutionary forces, and contextual ideas in 87 slogans from nine automotive brands sold in Indonesia: Toyota, Suzuki, Mitsubishi, Daihatsu, Honda, BMW, Mercedes Benz, Hyundai, and KIA were analyzed. It was discovered that low-priced car slogans are shorter, typically in phrase form, while expensive car slogans are longer and often in clause form. Despite the syntactic differences, both categories share similar illocutionary acts, predominantly representative acts aimed at informing consumers, building rapport, and enhancing the brands reputation. While directive acts are more persuasive, they can also be perceived as forceful, potentially creating a negative impression. The study highlights the importance of examining car slogans from a syntactic perspective, in addition to sociolinguistic and psycholinguistic angles. Additionally, the study explored how fantasy and hedonism are conveyed in slogans. Low-priced car slogans evoke close-to-reality fantasies with minimal use of adjective phrases and a weaker provocation of hedonism, whereas expensive car slogans offer symbolic fantasies, strongly provoking hedonism and encouraging indulgence in luxury, comfort, and independence, using both phrases and clauses with representative and directive acts. These findings suggest that car slogans make use of linguistic strategies that are conformed to fit the target market of a car.